A Case of Metanephric Adenoma Treated with Robotic-Assisted Laparoscopic Partial Nephrectomy - Segawa, Kohei (Hinyokika kiyo. Acta urologica Japonica, 2023)
A 53-year-old female patient was diagnosed with a left renal mass incidentally detected on an abdominal computed tomography (CT) scan. Further examination revealed a slightly contrast-enhancing mass 2.0 cm in diameter, in the left kidney on a contrast-enhanced CT scan. A diagnosis of left renal cell carcinoma (cT1aN0M0) was made and a robotic-assisted laparoscopic partial nephrectomy was performed. The excised tissue specimen exhibited a clearly circumscribed tumor. On hematoxylin eosin staining, the small uniform tumor cells appeared organized in glandular luminal arrangements, with lacking nuclear atypia and any malignant features. Immunostaining confirmed the diagnosis as metanephric adenoma, as indicated by positive results for WT1 and negative results for alpha-methylacyl-CoA race mase. Metanephric adenoma is an uncommon benign epithelial tumor of the kidney, which frequently poses a challenge in differential diagnosis with renal carcinoma on preoperative imaging. Pathologically, it can be challenging to differentiate from papillary renal cell carcinoma, and immunostaining can be used to effectively differentiate between the two entities